Edukasi Pencegahan Bullying Melalui Program Sekolah Ramah Anak pada Siswa SMP - Setia NIsa; Nela Novita Sari; Ratih Septiana Arpen; Hilma Yesi; Resi Citra M; Rika Armalini (Jurnal Medika: Medika, 2026)
Bullying is one of the problems that frequently occurs in the school environment and can have negative impacts on students’ mental health, self-confidence, and social development. Bullying behavior may take the form of physical, verbal, or psychological violence carried out repeatedly by individuals or groups against students who are considered weaker. The lack of students’ knowledge about the impacts of bullying and the low level of awareness regarding the importance of creating a safe and comfortable school environment are factors that contribute to the occurrence of bullying behavior. Therefore, educational efforts through a Child-Friendly School Program are needed to increase students’ understanding and awareness in preventing bullying. This community service activity aims to improve students’ knowledge and awareness regarding bullying prevention through education on the Child-Friendly School Program among students of SMP Negeri 1 Kota Pariaman. The implementation method consisted of preparation, implementation, and evaluation stages. The activity began with coordination with the school, followed by health education using lectures, discussions, and educational media presentations about bullying and its prevention. The evaluation of the activity was conducted through pretest and posttest to assess the improvement of students’ knowledge after the educational intervention. The results of the activity indicated an increase in students’ knowledge and understanding regarding the forms of bullying, its impacts, and ways to prevent bullying behavior in the school environment. In addition, students demonstrated more positive attitudes toward creating a safe, comfortable, and respectful school environment. This educational program is expected to serve as a promotive and preventive effort to support the implementation of a child-friendly school and reduce bullying incidents in the school environment.